(untitled) (Global Journal of Medical Research, 2016)
Background Paraphimosis is a surgical emergency in surgical practice A number of treatment options are available for treatment of paraphimosis including surgical and non surgical ones No randomized studies were undertaken to compare any treatment techniques of paraphimosis This study attempts to compare the outcome of injection of Hyaluronidase and Multiple puncture technique in the treatment of paraphimosis Materials and methods A randomized controlled study was undertaken in the surgery department of a medical college About 60 consecutive patients admitted with the history of paraphimosis were randomly divided into two groups One group received Hyaluronidase injection and another group had been treated by using multiple puncture technique The patients were followed on seventh day and six months after the surgery Results The study group included both pediatric and adult population About 43 3 of the patients in Hyaluronidase group and 60 in the multiple puncture technique group had the skin changes and edema was present in 83 3 of the Hyaluronidase and 87 7 of the multiple puncture technique group The outcome of the technique was 10 3 3 and 3 3 of the patients in the Hyaluronidase group had recurrence need for surgery and post operative pain About 13 3 13 3 and 16 7 of the patients in multiple puncture technique groups had recurrence need for surgery and post operative pain respectively Conclusion The injection Hyaluronidase was better than the multiple puncture technique in the treatment of paraphimosis